2011
DOI: 10.1007/s10903-011-9466-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ethnic Identity on Changes in High Risk HIV Behaviors in Sexually Active Migrant Workers

Abstract: Among migrant workers (MWs) in the US, HIV/AIDS prevalence may be as high as 13.5%. This serial cross-sectional study examines associations between Ethnic Identity (EI) in African American and Hispanic MWs and short-term changes in high-risk sexual behaviors. Baseline and 3-month follow-up data was collected from a larger HIV intervention study among MWs in Immokalee, Florida (n = 119) who reported unprotected sex in the past 30 days. The Multigroup Identity Measure was used to assess EI. A high EI score indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…Compared with the results in the previous studies in the US [23], our survey participants reported more accurate knowledge of condoms (e.g., their effectiveness against pregnancy and HIV, and the fact that their use should not be restricted to sex with prostitutes and between men). Despite this knowledge, however, the actual condom use among our survey participants was as low as among participants in previous studies [12,[14][15][16][17][18][19]23]. Our study also found MFWs' beliefs and cultural barriers lead to their hesitation to use condoms (e.g., condoms are uncomfortable, ''Mexican men don't like to use condoms'').…”
Section: Needs and Risks At The Individual And Country Levelcontrasting
confidence: 87%
See 2 more Smart Citations
“…Compared with the results in the previous studies in the US [23], our survey participants reported more accurate knowledge of condoms (e.g., their effectiveness against pregnancy and HIV, and the fact that their use should not be restricted to sex with prostitutes and between men). Despite this knowledge, however, the actual condom use among our survey participants was as low as among participants in previous studies [12,[14][15][16][17][18][19]23]. Our study also found MFWs' beliefs and cultural barriers lead to their hesitation to use condoms (e.g., condoms are uncomfortable, ''Mexican men don't like to use condoms'').…”
Section: Needs and Risks At The Individual And Country Levelcontrasting
confidence: 87%
“…This overlaps with the findings of the previous Canadian study [2,4,20], although it is impossible to compare the ratios as we did not include these questions in our survey. A cause for concern is that focus group participants, like their counterparts in the United States, reported potentially risky behaviour, including sex with multiple partners, transactional sex [12,18], and sex between men, possibly in part as a result of the imbalance between male and female workers [3,12], as well as low and inconsistent condom use [12,[14][15][16]19]. Compared with the results in the previous studies in the US [23], our survey participants reported more accurate knowledge of condoms (e.g., their effectiveness against pregnancy and HIV, and the fact that their use should not be restricted to sex with prostitutes and between men).…”
Section: Needs and Risks At The Individual And Country Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…We categorized the measures of acculturation into three groups: length of time living in the receiving culture and residency, language use and preference, and multi-faceted measures. Given that some multi-faceted measures include ethnic identity as a domain of acculturation, we categorized the two studies using the ethnic identity measure (Raffaelli, Zamboanga, & Carlo, 2005; Shehadeh et al, 2012) into the group of multi-faceted measures.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, many acculturation scales are multi-faceted and assess more than one domain relevant to cultural change (e.g., cultural knowledge, language use, social affiliations). Ethnic identity, the extent to which a person identifies with a particular culture, is another domain which has been employed to indicate acculturation (Shehadeh et al, 2012). Some established acculturation measures include identification of ethnicity as a dimension (e.g., Cuellar et al, 1995; Suinn, Rickard-Figueroa, Lew, & Vigil, 1987), although recent research suggests that ethnic identity and acculturation may represent different aspects of cultural identity (Schwartz, Zamboanga, & Jarvis, 2007).…”
Section: Introductionmentioning
confidence: 99%